EFFECTIVENESS OF ACUPUNCTURE IN FACIAL FUNCTION RECOVERY IN BELL'S PALSY PATIENTS: A CASE STUDY - Ronny Brayntin Rahail; Ronald Ronald; Ade Yuni Sahruni; Muktamar Umakaap; Febry Rahmadhani Suradji; Pricilya Margaretha Warwuru; Dani Nurcholis; Damaris Marlissa (Journal of Sport Science and Tourism Activity, 2026)
Bell's Palsy is a peripheral facial nerve palsy that causes unilateral weakness or paralysis of the facial muscles. This study aimed to analyze the effectiveness of acupuncture therapy in restoring facial motor function in Bell's Palsy patients. The study employed a case study design involving two Bell's Palsy patients who underwent acupuncture therapy at a sports health clinic in Merauke City. Both patients received 12 acupuncture sessions over six weeks (two sessions per week), with acupuncture points stimulated including ST4, ST6, ST7, GB14, BL2, GV26, and LI4. Facial function recovery was measured using the House-Brackmann Facial Grading System (HB-FGS) before and after the intervention. The first patient (male, 45 years, initial HB Grade IV) showed significant improvement to Grade II after 12 sessions. The second patient (female, 38 years, initial HB Grade III) achieved Grade I (normal) after 10 sessions. Both cases demonstrated that acupuncture is effective in accelerating facial function recovery in Bell's Palsy patients, with measurable improvements in HB-FGS scores, facial muscle strength, and facial expression symmetry. Acupuncture may be considered an effective complementary therapy modality in the management of Bell's Palsy.